(untitled) (Mustansiria Dental Journal, 2025)
The purpose of this study is to contrast the salivary levels of C-reactive protein between healthy controls and diabetic patients at various stages of periodontitis.Materials and methods: One hundred sixty men participated in this study; 32 of them were healthy control groups, while the other 128 men with type -2 diabetes were equally categorized into four groups according to stages of periodontitis (stage I, stage II, stage III, and stage IV). Following the collection of unstimulated salivary samples from each participant, (PPD, CAL, and BOP) clinical periodontal parameters were assessed. ELISA technique was used to measure the levels of CRP in saliva samples. Results: CRP was higher in diabetic patients with all stages of periodontitis than healthy controls. The level of CRP is increased when periodontitis progresses to higher stages. Stage IV group (515.33±258.51), stage III group (315.52±206.71), stage II group (206.61±124.64), stage I (160.07±97.49), control group (45.63±25.29) in which their salivary levels were the least with significant differences among the groups (p=0.000).Conclusion: The inflammatory marker CRP is increased in diabetic patients than in Control, especially when the stage of periodontitis gets worse.